Good fortune [videorecording (DVD)] - Ansari, Aziz, 1983-; Ansari, Aziz, 1983-; Rogen, Seth, 1982-; Palmer, Keke; Oh, Sandra, 1971-; Reeves, Keanu; Burwell, Carter; Napier, April; Newport-Berra, Adam (Lionsgate, 2025)
"A well-meaning but rather inept angel named Gabriel observes a struggling gig worker, Arj, who is barely making ends meet in Los Angeles, and intervenes to show him that money can't solve all his problems. Gabriel swaps Arj's life with a wealthy venture capitalist's, Jeff--but the plan backfires when Arj is convinced his newfound wealth has, in fact, solved all his problems. As Arj refuses to switch back, Jeff is left without his fortune, Gabriel loses his wings, and all three are forced to confront what it truly means to be human."--